Influence of Nape Cluster Acupuncture on Peripheral Plasma ET Content in Patients with Acute Cerebral Infarction - 周鸿飞 王恩龙 徐锦平 曹铁军 黄国琪（Translator） (Journal of acupuncture and tuina science, 2006)
Objective: To investigate the mechanism of nape cluster acupuncture in the treatment of acute cerebral infarction.Methods: Eighty patients with acute cerebral infarction were selected and randomly allocated to group A and B. Group B was given routine treatment for acute phase and Group A was added with the nape cluster acupuncture based upon the treatment for Group B. The treatment was given twice daily, with 15 d as a course of the treatments, to observe the decreasing situation in the score of the nerve function defects and changes in plasma ET content.Results: There were significant differences in the score of the nerve function defects and plasma ET content before and after treatments in two groups (P<0.05), but there was significant difference between Group A and Group B after treatment (P<0.05), indicating the curative effect was better in Group A than in Group B.Conclusion: Nape cluster acupuncture can be used to effectively treat acute cerebral infarction and obviously decrease plasma ET content and reduce the score of the nerve function defects. The findings also proves that the therapeutic effect was obviously better than single medication, if nape cluster acupuncture was combined in the treatment of the acute cerebral infarction.